Female reproductive health in two lamp factories: effects of exposure to inorganic mercury vapour and stress factors. Issue 7 (July 1985) - De Rosis, F; Anastasio, S P; Selvaggi, L; Beltrame, A; Moriani, G
Abstract : To evaluate the possible influence of mercury vapour on female reproduction, 153 women working in a mercury vapour lamp factory have been compared with 193 women employed in another factory of the same company, where mercury was not used. Both groups of subjects were exposed to stress factors (noise, rhythms of production, and shift work). The production process has been analysed by inspection of the plants and by collective discussions with "homogeneous groups" of workers; a retrospective inquiry into work history and reproductive health events has been subsequently performed by an individual interview. Women exposed to mercury vapour currently not exceeding the time weighted average air concentration of 0.01 mg/m3 declared higher prevalence and incidence rates of menstrual disorders, primary subfecundity, and adverse pregnancy outcome; however, the progression of these problems with the level of exposure to mercury inside the same factory was not always clear. The results of this study neither prove nor exclude the possibility that occupational exposure to this concentration of mercury has a negative effect on female reproduction.